The last hero Wild Bill Donovan - Brown, Anthony Cave 1929-2006 (Times Books, 1982)
The biography and political experience of Major General William J. Donovan, founder of the OSS and "father" of the CIA, from his personal and secret papers and the diaries of Ruth Donovan.
Keywords: Donovan, William J. -- (William Joseph) -- 1883-1959; Donovan, William J. -- 1883-1959; USA -- Central Intelligence Agency; Geschichte; Intelligence officers -- United States -- Biography; USA; Biografie